Production of chlorophyll-rich powder from Moringa oleifera leaves using dehumidification and intermittent drying: impact on drying characteristics and chlorophyll retention. - Djaeni, M.; Hadiyanto, H.; Suherman, S.; Handayani, N. A.; Utari, F. D. (International Journal of Agricultural Technology, 2025)
Results demonstrated that zeolite enhanced moisture removal efficiency, with significant reductions in moisture ratios which observed at higher temperatures. Specifically, at 40°C, the moisture ratio improved from 0.9175 to 0.8924, while at 80°C, it decreased from 0.8039 to 0.6275. Intermittent tempering further optimized moisture removal, achieving a moisture ratio of 0.4199 with a 20-minute tempering period at 60°C. The study employed the Henderson & Pabis model which achieved high predictive accuracy for drying characteristics. Notably, chlorophyll retention was maximized at lower temperatures and optimal tempering durations. Overall, this research underscored the potential of combining zeolite and intermittent drying techniques to enhance moisture removal and preserve chlorophyll, offering a practical solution for producing high-quality Moringa leaf powder in both small-scale and industrial settings.